Pulmonary Chondroid Hamartoma With Nontuberculous Mycobacterial Infection. Issue 14 (April 2015) - Lee, Yong Chul; Moon, Jin Chang; Gang, Su Jin; Park, Seung Yong; Kim, So Ri; Dessein., Rodrigue
<x xml:space="preserve">Abstract</x> Abstract Solitary pulmonary nodules (SPNs) can be manifested in a variety of disorders including neoplasms, infection, inflammation, and vascular or congenital abnormalities. In addition, they are often accompanied with other pulmonary pathologic lesions such as consolidations and several pulmonary disorders present as similar pulmonary nodular lesions simultaneously. Diagnostic workup is important for these SPNs; however, many physicians often miss the second diagnosis for multiple pulmonary lesions with SPNs due to lack of clinical suspicion that each pulmonary nodule or pathologic lesion can have each other's diagnosis. Herein, we report 2 cases of coexistence of pulmonary chondroid hamartoma with nontuberculous mycobacterial (NTM) infection presenting as pulmonary nodules and multiple consolidative lesions. A 60-year-old man was admitted for the evaluation of multifocal pulmonary lesions including SPN with chronic exertional dyspnea. Multiple lung tissues were obtained from each lesion through percutaneous transthoracic needle biopsy (PTNB). At the same time, bacteriologic examination was performed using respiratory samples obtained by bronchoscopy. Based on pathologic and microbiologic results, the patient diagnosed as pulmonary chondroid hamartoma with pulmonary NTM infectious disease. In addition, a 56-year-old woman visited for the evaluation of a small SPN. The SPN was resected surgically for the pathologic examination and turned out to be pulmonary chondroid hamartoma. Interestingly, the diagnostic workup revealed that the patient had Lady Windermere syndrome which is one of features for Mycobacterium avium complex (MAC) pulmonary disease. Both patients were treated with the standard antibiotics against MAC as recommended by the ATS/IDSA guideline. This is the first report of 2 patients, as far as we know, that chondroid hamartoma and NTM disease develop simultaneously in the lung. This report emphasizes that physicians should endeavor to confirm the individual diagnosis for the various pulmonary abnormal lesions detected at the same time, if necessary through multifocal biopsies for each lesion.